Change in cholesterol absorption and synthesis markers in patients with coronary heart disease after combination therapy with simvastatin plus ezetimibe - ZHANG, Tao; WU, Wen-feng; LIU, Yang; WANG, Qi-hui; WANG, Lü-ya; MI, Shu-hua (Chinese medical journal, 2013)
Bad, round Statins and ezetimibe have been reported to change the balance of cholesterol metabolism, but few studies have been performed on Chinese patients. The aim of this study was to evaluate changes in cholesterol metabolism markers in patients with coronary heart disease. Methods Forty-five patients with coronary heart disease were treated with 20 mg/d of simvastatin for four weeks. Subjects were then divided into two different therapy groups according to whether they reached the target values for total cholesterol and low density lipoprotein cholesterol level. Patients who reached the target values remained on simvastatin and those who did not reach the target values took a combination of simvastatin plus 10 mg/d ezetimibe until the 12th week. The concentrations of cholesterol synthesis markers （lathosterol and desmosterol） and absorption markers （campesterol and sitosterol） were measured on the 1st, 4th, and 12th week of the study by gas chromatography. Results After treatment with simvastatin for four weeks, the levels of total cholesterol and low density lipoprotein cholesterol decreased significantly compared to levels measured during the 1st week （P 〈0.05）. On the 12th week the levels of total cholesterol and low density lipoprotein cholesterol had decreased significantly （P 〈0.001） compared to levels during the 4th week. By the 12th week the levels of campesterol and sitosterol in the combination group had decreased significantly （P〈0.05） compared with levels measured during the 4th week. Conclusions Coronary heart disease patients with high cholesterol synthesis at baseline might gain a greater benefit from simvastatin treatment. Combination therapy with simvastatin plus ezetimibe in patients with low cholesterol synthesis at baseline might increase the success rate of lipid-lowering throuah decreasing the absorption of cholesterol.